Geochemistry of major and trace elements in sediments from the Lubei Plain, China: Constraints for paleoclimate, paleosalinity, and paleoredox environment - Zou, Chunhui; Mao, Longjiang; Tan, Zhihai; Zhou, Liang; Liu, Lu (Journal of Asian Earth Sciences: X, 2021)
•Two large-scale transgressions are recognized in Sr/Ba and Rb/K curves.•Multiple elementary ratios are used to reconstruct the sedimentary environment.•Holocene climate change in the Lubei Plain is comparable to that in the whole China. As has been greatly affected by sea-level fluctuations since the Holocene, the Lubei Plain is featured by typical marine and alluvial deposits that records abundant information on the environmental evolution. In this context, the Lubei Plain is a sensitive zone in response to global climate change. In this study, we comprehensively logged a section, here in the the CY section, which is 4.4 m long and corresponds to a time interval of 5250a according to the OSL dating. This section is divided into five sub-sections based on the features of the proxies for paleoclimate, paleosalinity, and paleoredox environment, which are labeled as stages V to I, respectively. The sediment of stage V (5250-3850a) is featured by low Rb/Sr and Mg/Ca ratios that show similar variation trends, which indicate a progressively arid climate with high precipitation. The deposition of stage IV (3850-3260a) is suggested to occur in a warm-wet, brackish-water environment, with sub-reduction to oxidation conditions. When it comes to stage III, its deposition (3260-2950a) is indicated to occur in a drier climate and less saline environment than stage IV, accompanied by sub-reduction conditions. As for stages II (2950-1580a) and I (1580a to present), their deposition occurs in a wet-to-dry transitional climate, which is concomitant with decreased water salinity, enhanced oxygen enrichment, gradual sea-level drop, and northward marine regression. Eventually, it is determined that various sedimentary facies alternatively take dominance since 5250a, including coastal-tidal flat facies, shallow marine facies, alluvial facies, tidal flat facies, and fluvial facies.